Children's agency in reducing poverty and environmental risks : Case study of the Education for Income Program at Lighthouse Institute, Harare - Lombard, A. (Antoinette) (University of Pretoria, 2021)
Mini Dissertation (MSW (Social Development and Policy))--University of Pretoria, 2020.